An overview of general practitioner consultations in China: a direct observational study. (20th April 2020) - Zhong, Chenwen; Luo, Zhuojun; Liang, Cuiying; Zhou, Mengping; Kuang, Li
Abstract: Background: General practitioner (GP) consultation has long been considered an important component of general practice, but few studies have focused on its characteristics in China. Objective: This study aimed to explore the content and elucidate the characteristics of GP consultations in general practice in China. Methods: A multimethod investigation of GP consultations in eight community health centres in Guangzhou and Shenzhen, China was conducted between July 2018 and January 2019. Data from 445 GP consultations were collected by direct observation and audio tape and analysed by a modified Davis Observation Code with indicators for frequencies and detailed time durations. GP and patient characteristics were collected by post-visit surveys. Results: The mean visit duration was approximately 5.4 minutes. GPs spent the most time on treatment planning, history taking, negotiating, notetaking and physical examination and less time on health promotion, family information collecting, discussing substance use, procedures and counselling. The time spent on procedures ranked first (66 seconds), followed by history taking (65 seconds) and treatment planning (63 seconds). Besides, patients were very active in the consultation, specifically for topics related to medicine ordering and drug costs. Conclusions: This study described the profile of GP consultations and illustrated the complexity of care provided by GPs in China. As patient activation in GP consultations becomes increasingly important, future studies need to explore how to promote the engagement of patients in the whole consultation process other than just requesting for medicine.